Principles of French law - Bell, John 1953- (Oxford University Press, 2008)
Offering students and lawyers an introduction to the French law and legal system, this text gives an explanation of the French institutions, concepts, and techniques, providing a clear sense of the questions which French lawyers see as important
Includes bibliographical references and index
Keywords: Recht; Frankreich; Law / France; Justice, Administration of / France; Law; France; Justice, Administration of; France; Einführung